Corporate governance in asia: a comparative study - N, Thiyagu; Ravindran, Priyanka; S, Rajalakshmy (Journal of Management and Science, 2013)
This study examines the overview of Corporate Governance practices in Asian countries. However the corporate governance is a mandatory requirement in today‘s corporate world by every stake holders groups. Moreover, corporate governance has brought weakness to the attention of general public, especially in Asian countries.This paper begins with a corporate governance needs and overview of corporate governance practices as approved by the OECD and World Bank. Then proceeds to examine how these practices are being useful for Asian countries.